Jian dan zuo zao can, duo shui 10 fen zhong - Sabadina (Beijing: China Light Industry Press, 2022)
This book introduces the cooking methods of different breakfasts, divided into six parts: soup porridge, rice and pasta, sandwiches and salads, snacks, drinks, and super simple set menus, each recipe has a step-by-step chart, cooking cheats, cooking difficulty and cooking time guidelines.
Text in simplified Chinese script.
Keywords: Breakfasts; Cookbooks